Villgro Innovation Marketing Private Limited : building last mile delivery model using entrepreneurs - Bhamoriya, Vaibhav (SAGE knowledge. Cases., 2016)
Ashutosh Sinha is managing VIMPL as a rural distribution business involving Villgro stores and village level entrepreneurs (VLEs). After spending two years in evolving the business model which provides sustainable products to improve rural livelihood, he has recently started selling FMCG products through the VIMPL network. As he decides to expand the business, he has to make choices about strategic path of horizontal expansion versus vertical expansion. The case provides a detailed description of VLE operations and examines the challenges in building delivery models using entrepreneurs.